Implementation of Inclusive Education in Elementary Schools - Muhammad Asyam; Danniel Peavey Ady Wicaksono; Suparmi (Aslim: Journal of Education and Islamic Studies, 2024)
This study aims to examine the concept of inclusive education at the primary school level and identify the challenges faced in its implementation. This research uses the literature review method by analyzing various literature sources, such as journals, books and official documents related to inclusive education. The results show that inclusive education in primary schools still faces obstacles, such as limited infrastructure, lack of teacher training and a curriculum that is not responsive to students' needs. To overcome this, intensive collaboration between schools, parents and communities is needed to improve the effectiveness of inclusive programs.